Remarkable rutin-rich Hypericum capitatum extract exhibits anti-inflammatory effects on turpentine oil-induced inflammation in rats - Farcas, Anca D. (BMC Complement Altern Med, 2019)
BACKGROUND: Natural extracts with beneficial biological activities are nowadays of high interest, in various treatment or prophylaxis. Hypericum capitatum has been known for its curative effects for centuries and its extracts have become of interest due to their distinct activity among other Hypericaceae members. In this study, further light is aimed to be shed on the secondary-metabolites composition of H. capitatum extracts, using chromatographic techniques and Electron paramagnetic resonance profiles in alkaline medium. Considering that no previous works explored the anti-inflammatory activity of H. capitatum, here, an in vivo study is also designed in order to evaluate this property by assessing the impact of one of H. capitatum extracts in ameliorating turpentine oil-induced inflammation on rats and to quantify their blood antioxidants level. METHODS: Chromatographic techniques and Electron paramagnetic resonance spectroscopy were used in order to describe the chemical profile in different parts of the plant. The in vivo study on turpentine-oil induced inflammation in rats included three doses of H. capitatum extract expressed in rutin concentration. Oxidative stress was measured using total oxidative status, total antioxidant capacity, oxidative stress index, 3-nitrotyrosine, nitric oxide, malondialdehyde, superoxide dismutase, catalase and the inflammatory response was evaluated by performing a complete blood cells count and C reactive protein. RESULTS: The extract was remarkably rich in rutin; however, other polyphenolic-like minor components appeared important in explaining the observed biological properties. The tested extract prevents the increase of inflammation-induced white blood cell count, number of neutrophils, and serum nitric oxide, and did so in a dose-dependent manner, similarly to the positive control—diclofenac. In addition, the same extract appeared to be a good alternative to diclofenac to restore total oxidative status, thiobarbituric active reactive species, total proteins and C reactive proteins. Moreover, antioxidant enzymes such as catalase, superoxide dismutase and total serum thiol concentration were significantly increased by the tested extract. CONCLUSIONS: Due to its powerful reservoir rich in rutin, H. capitatum extract depicted its in vivo antioxidant and anti-inflammatory effects indicating it to be a good alternative to conventional drugs for oxidative stress protection.